The Influence of Digital Literacy, Technology Integration, Technological Acceptance Model, and Brand Image on Purchase Decisions at Yamaha Dealers in Indonesia - Indah Kartika Hakim (Budapest International Research and Critics University, 2022)
This research objectives to find out the effect of digital literacy, technology integration, technological acceptance model, and brand image on purchasing decisions at Yamaha dealers in Indonesia. The research was conducted by distributing questionnaires using a google form to respondents throughout Indonesia. The sampling technique used is probability sampling, using random sampling. The research data analysis technique used Partial Least Square-Structural Equation Modeling. The findings show that Digital Literacy, Technology Integration, Technological Acceptance Model, and Brand Image positively affect purchasing decisions.